Freedom of Religion and the headscarf: a perspective from international and comparative constitutional Law - Osman, Fatima (Department of Public Law, 2021)
his thesis analyses whether a legislative ban on wearing a headscarf breaches the right to freedom of religion, as such right is universally understood. It describes the ambit of the right to freedom of religion by examining the theoretical justification and importance of the right and thereafter analysing how the right is recognised in international and regional treaties and domestic constitutions. It demonstrates that religious freedom comprises of the right to hold a religion and the right to manifest a religion in the form of worship, observance, practice and teaching. Religious freedom, however, is not absolute and the thesis explains in the light of international and comparative case-law that the right to freedom of religion may be limited by a law that pursues a legitimate state interest and is reasonable. In light of this theoretical framework the thesis examines the practice of Muslim women wearing a headscarf and argues that the practice constitutes a manifestation of Islamic belief protected by the right to freedom of religion. Thereafter this thesis examines French, Turkish and German prohibitions on wearing a headscarf, the effect of these laws on Muslim women and the justifications furnished for such laws. It is argued that the state interest of preserving secularism relied upon to justify a headscarf ban is not legitimate and does not justify a headscarf ban. Furthermore, even where the state has a legitimate interest in preventing the coercion of young girls, promoting the equality rights of women and maintaining safety and order, a headscarf ban does not constitute a reasonable limitation of religious freedom. Ultimately, this thesis argues that a headscarf ban exacerbates the problems it is meant to solve and constitutes an unjustifiable infringement of religious freedom.